Nerve growth factor delivery by ultrasound-mediated nanobubble destruction as a treatment for acute spinal cord injury in rats - Song Z (Dove Medical Press, 2017)
Zhaojun Song,1 Zhigang Wang,2 Jieliang Shen,1 Shengxi Xu,1 Zhenming Hu1 1Department of Orthopedics, The First Affiliated Hospital, 2Institution of Ultrasound Imaging, The Second Affiliated Hospital, Chongqing Medical University, Chongqing, People’s Republic of China Background: Spinal cord injuries (SCIs) can cause severe disability or death. Treatment options include surgical intervention, drug therapy, and stem cell transplantation. However, the efficacy of these methods for functional recovery remains unsatisfactory. Purpose: This study was conducted to explore the effect of ultrasound (US)-mediated destruction of poly(lactic-co-glycolic acid) (PLGA) nanobubbles (NBs) expressing nerve growth factor (NGF) (NGF/PLGA NBs) on nerve regeneration in rats following SCI. Materials and methods: Adult male Sprague Dawley rats were randomly divided into four treatment groups after Allen hit models of SCI were established. The groups were normal saline (NS) group, NGF and NBs group, NGF and US group, and NGF/PLGA NBs and US group. Histological changes after SCI were observed by hematoxylin and eosin staining. Neuron viability was determined by Nissl staining. Terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick end labeling staining was used to examine cell apoptosis. NGF gene and protein expressions were detected by quantitative reverse transcription polymerase chain reaction and Western blotting. Green fluorescent protein expression in the spinal cord was examined using an inverted fluorescence microscope. The recovery of neural function was determined using the Basso, Beattie, and Bresnahan test. Results: NGF therapy using US-mediated NGF/PLGA NBs destruction significantly increased NGF expression, attenuated histological injury, decreased neuron loss, inhibited neuronal apoptosis in injured spinal cords, and increased BBB scores in rats with SCI. Conclusion: US-mediated NGF/PLGA NBs destruction effectively transfects the NGF gene into target tissues and has a significant effect on the injured spinal cord. The combination of US irradiation and gene therapy through NGF/PLGA NBs holds great promise for the future of nanomedicine and the development of noninvasive treatment options for SCI and other diseases. Keywords: nanobubbles, nerve growth factor, spinal cord injury, apoptosis, gene therapy